Holding It Down? The Silencing of Black Female Students in the Educational Discourses of the Greater Toronto Area - George, Rhonda C. (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
This article grapples with the ways in which Black female students tend to be obscured from the discourses around the educational experiences and outcomes of Black students in the Greater Toronto Area (GTA). I employ intersectionality as a theoretical frame, using content analysis and case study approaches to elucidate the mechanics of how these absences and silences persist in the national, provincial, and local contexts in which they occur. Despite the necessity and validity of research on the various educational experiences of Black GTA students, I find that the research tends to focus primarily on Black males, often using their narratives to define the experiences of all Black students in the region. I also find that it is in the very methodological questions and applications of those methodological approaches, that this exclusion of Black female students takes place, creating and maintaining gaps and silences in the scholarship, resulting in the absence of vital sociological knowledge. The implications and potential negative effects of the normalization and perpetuation of this exclusion on Black female students and their mental and physical well-being is also explored. I conclude by calling for reflexivity and a rethinking of current methodological approaches in this context in order incite more inclusive and fulsome engagement with the educational experiences of Black female students. Keywords: intersectionality, race, education, Black female students, Greater Toronto Area, sociology of education, research methodology